Analisis Hukum Terhadap Tindak Pidana Penyerobotan Lahan Di Indonesia - Muhammad Jarnawansyah (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
This legal journal explores the intricate legal landscape surrounding the criminal act of land encroachment in Indonesia. Combining normative legal analysis and empirical case studies, the research delves into the legal framework governing land encroachment, challenges in law enforcement, and efforts to enhance legal efficacy. The findings offer profound insights and concrete recommendations to fortify the legal system and enforcement mechanisms against land encroachment.